The heart of sustainability - Lim, Jaslyn Hui Ting (2012)
Prior researches have vague and abstract definitions of the concept of the “core” of business and the process of applying sustainability at the core was also undefined. This study seeks to create a clearer understanding of integrating sustainability to the core of the business through the construction of the Heart of Sustainability (HOS) model. A deeper understanding of sustainability in three companies (namely DHL, Siloso Beach Resort (SBR) and National Library Board (NLB)) was also achieved through interviews and site visits. They were selected based on their outstanding performance in sustainability as they are recognised as winners of the Singapore Sustainability Awards 2011. Even though all three companies are from different industries, a standardized set of questions were asked during the interview to gain new insights from them.